Autonomous vehicle experiments and the city. Issue 3 (16th March 2022) - Dowling, Robyn; McGuirk, Pauline
ABSTRACT: As part of the infiltration of automation across urban life, autonomous vehicles (AVs) are traversing cities and regions across the world. This paper presents our critical analysis of trials of these vehicles, which are being shaped by, and are shaping, the material, political, and economic fabric of the city. We take the burgeoning literature on urban experimentation in a new empirical direction – that of mobility – and deepen understanding of the sense in which such experiments are urban. Our extensive analysis of global experiments with automated vehicles provides an analytical typology of four forms of experimentation – on-road, test bed, precinct, and living lab – each with differing relations to the city and differing potentials for political transformation. We illuminate the city as much more than a container for experiments, being multiply implicated in these AV trials through which, we argue, differentiated conditions of possibility emerge for contesting and reconfiguring the city's "automobility."